2022
DOI: 10.5888/pcd19.220112
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Among Adults in Rural Western North Carolina During the COVID-19 Pandemic

Abstract: Introduction During the COVID-19 pandemic, measures implemented to protect community health may have influenced how and where people engaged in physical activity. In rural communities, access to resources, the environment, and socioeconomic status could play a role in how adults are physically active. Our study examined locations where rural residents of a county in western North Carolina engaged in physical activity early in the COVID-19 pandemic, their reasons for being physically active, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Aligning with national and global trends [4], the findings point to a perceived negative impact of COVID-19 on PA participation-nearly half of participants described pandemic-related barriers that made PA more difficult and reported being less active during the height of the pandemic. Several of the pandemic-related barriers to PA (i.e., increased stress and anxiety, lack of facilities to partake in PA, fear of exposure to COVID-19, and discomfort wearing a face mask) found in these communities were similar to those reported in other studies [12,13,28] with different samples (mostly White, income > USD 60,000 [13], and not rural [12]). On the contrary, the other half of the study sample reported that the COVID-19 pandemic did not make it more difficult to be active.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Aligning with national and global trends [4], the findings point to a perceived negative impact of COVID-19 on PA participation-nearly half of participants described pandemic-related barriers that made PA more difficult and reported being less active during the height of the pandemic. Several of the pandemic-related barriers to PA (i.e., increased stress and anxiety, lack of facilities to partake in PA, fear of exposure to COVID-19, and discomfort wearing a face mask) found in these communities were similar to those reported in other studies [12,13,28] with different samples (mostly White, income > USD 60,000 [13], and not rural [12]). On the contrary, the other half of the study sample reported that the COVID-19 pandemic did not make it more difficult to be active.…”
Section: Discussionsupporting
confidence: 83%
“…The first US-based study to examine COVID-19 ′ s impact on meeting PA guidelines in rural and non-rural residents found that rural participants were significantly less physically active than their non-rural counterparts, and participants who reported lack of indoor space as a barrier to PA were 93% less likely to meet PA guidelines than those who did not indicate lack of indoor space as negatively impacting PA [12]. A separate cross-sectional study in rural western North Carolina [13] found that the closure of parks and recreation centers (71.9%), stay-at-home orders (55.7%), cancellation of recreational sports (48.8%), and fitness facility closings (44.9%) were the most commonly reported barriers to PA. However, data for both studies were collected from mostly white participants (95.7% and 96%, respectively) and may not be generalizable to other racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…This year’s winning paper in the undergraduate category was generated by Creech et al: “Physical Activity Among Adults in Rural Western North Carolina During the COVID-19 Pandemic” ( 5 ). This article examines the locations, reasons, benefits, and barriers to engaging in physical activity among adults living in rural communities during the COVID-19 pandemic.…”
Section: Winners and Submissionsmentioning
confidence: 99%
“…Over the years, PCD has refined the purpose of the student research publication opportunity to include these 5 primary goals (3): Sixteen student research papers were submitted for the contest in 2022, and all submissions underwent the same peer-review process as any other manuscript submitted to the journal for consideration. Eight of the 16 papers were successful in making it through a rigorous review process before being accepted for publication (4)(5)(6)(7)(8)(9)(10)(11). Student research papers addressed a range of topics: COVID-19 and various aspects of health, food insecurities among caregivers in southern states, the relationship between physical activity and depression among high school students, perceptions of neighborhood development on active living among community residents, use of a cancer index as a predictor of common cancers, and spatial analysis of breast cancer mortality rates in rural states.…”
Section: Goals and Submission Requirementsmentioning
confidence: 99%
See 1 more Smart Citation